Five little Peppers in the Little Brown House - Sidney, Margaret, 1844-1924; Heyer, Hermann, 1876-1950 (Salt Lake City, UT : Project Gutenberg, 2023)
"Five Little Peppers in the Little Brown House" by Margaret Sidney is a children's novel published in 1907. Part of the beloved Five Little Peppers series, this book returns to the humble origins where the Pepper family's story began. Despite now living in luxury with their wealthy benefactor Mr. King, the five Pepper children's hearts remain tied to their original home. The story explores how the values of hard work, humility, and togetherness instilled by their mother continue to guide them, even as they navigate their unique position between working-class roots and upper-class surroundings. (This is an automatically generated summary.)
Polly Pepper's chicken pie -- Phronsie's new shoes -- The little tin plate -- In Deacon Blodgett's barn -- Baking day -- The little white cat -- Spending the day at the Beebes' -- At the Peters farm -- Over at Grandma Bascom's -- The stage ride -- A little yellow chicken -- At the parsonage -- Company at the little brown house -- In Doctor Fisher's gig.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Five_Little_Peppers
Release date is 2023-07-06
Donald Cummings, David E. Brown, Sue Clark, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Siblings -- Juvenile fiction; Families -- Juvenile fiction; Fatherless families -- Juvenile fiction; Five Little Peppers (Fictitious characters) -- Juvenile fiction